The library book [compact disc, unabridged] - Orlean, Susan (Audioworks, imprint of Simon & Schuster Audio, 2018)
Susan Orlean re-opens the unsolved mystery of the most catastrophic library fire in American history, and delivers a dazzling love letter to the beloved institution of libraries.